2021
DOI: 10.4028/www.scientific.net/kem.892.51
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Deformation and Fatigue of Semi Flexible Pavement Incorporating Waste Tire Rubber and Natural Zeolite

Abstract: Due to repeated loads, the pavement structures will experience repeated stresses and strains resulting in permanent deformation even though the working loads are still smaller than the design load. The permanent deformation will lead to cracking and fatigue failure with the life of the pavement. This phenomenon can be reduced by increasing the stiffness, flexibility, durability, stability and water absorption of the pavement. Material modification including the utilization of waste tire rubber (WTR) and natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…This contributes to an increase in the cement grouts' density and, hence, causes an increase in the compressive strength of semi-flexible mixtures. The increase in waste tire rubber powder also causes improvement in compressive strength [109]. The behavior of improvement in flexural strength due to waste tire rubber and zeolite mineral was observed as quite similar to the compressive strength.…”
Section: Compressive and Flexural Strengthmentioning
confidence: 64%
See 2 more Smart Citations
“…This contributes to an increase in the cement grouts' density and, hence, causes an increase in the compressive strength of semi-flexible mixtures. The increase in waste tire rubber powder also causes improvement in compressive strength [109]. The behavior of improvement in flexural strength due to waste tire rubber and zeolite mineral was observed as quite similar to the compressive strength.…”
Section: Compressive and Flexural Strengthmentioning
confidence: 64%
“…The behavior of improvement in flexural strength due to waste tire rubber and zeolite mineral was observed as quite similar to the compressive strength. The flexural strength of semi-flexible mixtures increased with increasing zeolite content up to 15% [109].…”
Section: Compressive and Flexural Strengthmentioning
confidence: 97%
See 1 more Smart Citation
“…It shows that when the tire rubber powder content is 5% and the zeolite content is 15%, the mechanical properties of SFP are the best. In terms of compressive strength, Hamzani et al [20] injected cement mortars containing 0%, 5%, 10%, 15%, and 20% natural zeolite into porous asphalt specimens according to ASTM C670-91a at 14 days of age. Te compressive strength test was carried out on the above, and the test results showed that when the natural zeolite content was 15% and the waste tire rubber content was 5%, the compressive strength reached 15.43 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…These pavements have the combined advantages of conventionally flexible and rigid pavements for rutting-and moisturerelated damage, joint-free pavement, resistance to fuel spillage, and can be opened to traffic within 24 h [3]. However, the overall performance of semi-flexible pavement is a function of aggregate type and gradation, the composition of cement grout, material stiffness properties, and testing conditions [4].…”
Section: Introductionmentioning
confidence: 99%